Aplasia cutis congenita: A case report (Indian Journal of Case Reports, 2019)
Aplasia cutis congenita (ACC) is a congenital absence of skin most commonly involves the scalp. There is no definite etiology available, but multiple causes such as intrauterine infection, fetal exposure to cocaine, heroin, alcohol or antithyroid drugs, vascular disruption, genetic causes, syndromes, and teratogens have been suggested. Here, we report the case of a late preterm male baby weighing 1.9 kg born at 36 weeks of gestation to a third gravida mother with a previous history of one stillbirth and one baby’s death on day 3 of life. Multiple well-demarcated raw areas showing an absence of skin over the neck, extremities and back of varying diameter were seen. X-ray showed features suggestive of pyloric stenosis and ultrasound of the abdomen showed bilateral hydronephrosis. A skin biopsy showed a full-thickness absence of skin and dermal appendages in the involved areas, with dermis and epidermis ending abruptly. A final diagnosis of ACC was made based on the investigations. ACC of the trunk is less common than scalp, and different clinical presentations may be seen in infants with aplasia cutis.